Taenia saginata: A Rare Cause of Gall Bladder Perforation - Suhail Yaqoob Hakeem; Arshad Rashid; Suhail Khuroo; Rajandeep Singh Bali (Case Reports in Surgery)
We report a case of biliary peritonitis caused by gall bladder perforation due to Taenia saginata induced gangrenous cholecystitis. Although parasites are not unusual causes of biliary tract disorders, especially in disease endemic areas, but this is for the first time that Taenia saginata has been reported to cause gall bladder perforation.